NOTES ON MAPANIA LATIFOLIA UITTIEN (CYPERACEAE) FROM LONG BANGA, SARAWAK - Miraadila, M. I.; Zinnirah, Shabdin; Kalu, Meekiong; Ivy Geradlyn, N.; Yazid, K. (Forest Department Sarawak, 2020)
Cyperaceae is one of the largest family in the Monocotyledon plant group consisting of 106 genera and approximately 5600 species throughout the world. Mapania is among the important understory genus in this family. To-date about 40 species of Mapania have been recorded for Sarawak that includes 13 newly described species. Mapania latifolia is one of four species with foliaceous involucral bract recorded in Southeast Asia and its distributed in Peninsular Malaysia and Borneo. This species tends to show tremendous variations among the populations from different elevations and localities. This preliminary study is to investigate the variation of M. latifolia from Long Banga and to compare it with the collections from other places in the Heart of Borneo project areas.